Basic Fibroblast Growth Factor Regulates REX1 Expression Via IL‐6 In Stem Cells Isolated From Human Exfoliated Deciduous Teeth. Issue 6 (29th December 2016) - Nowwarote, Nunthawan; Sukarawan, Waleerat; Pavasant, Prasit; Osathanon, Thanaphum
ABSTRACT: Basic fibroblast growth factor (bFGF) regulates pluripotent marker expression and cellular differentiation in various cell types. However, the mechanism by which bFGF regulates REX1 expression in stem cells, isolated from human exfoliated deciduous teeth (SHEDs) remains unclear. The aim of the present study was to investigate the regulation of REX1 expression by bFGF in SHEDs. SHEDs were isolated and characterized. Their mRNA and protein expression levels were determined using real‐time polymerase chain reaction and enzyme‐linked immunosorbent assay, respectively. In some experiments, chemical inhibitors were added to the culture medium to impede specific signaling pathways. Cells isolated from human exfoliated deciduous tooth dental pulp tissue expressed mesenchymal stem cell surface markers (CD44, CD73, CD90, and CD105). These cells differentiated into osteogenic and adipogenic lineages, when appropriately induced. Treating SHEDs with bFGF induced REX1 mRNA expression and this effect was attenuated by pretreatment with FGFR or Akt inhibitors. Cycloheximide pretreatment also inhibited the bFGF‐induced REX1 expression, implying the involvement of intermediate molecule(s). Further, the addition of an IL‐6 neutralizing antibody attenuated the bFGF‐induced REX1 expression by SHEDs. In conclusion, bFGF enhanced REX1 expression by SHEDs via the FGFR and Akt signaling pathways. Moreover, IL‐6 participated in the bFGF‐induced REX1 expression in SHEDs. J. Cell. Biochem. 118: 1480–1488, 2017. © 2016 Wiley Periodicals, Inc. Abstract : bFGF signals through the FGF receptor, activating the MAPK and AKT intracellular signaling pathways, and inducing the expression and secretion of IL‐6. Extracellular IL‐6 then stimulates the expression of REX1 as demonstrated.